Iconographic Exegesis of the Hebrew Bible / Old Testament An Introduction to Its Method and Practice (Vandenhoeck & Ruprecht, 2015)
Biographical note: Izaak J. de Hulster is currently a post-doc at the University of Göttingen, Germany. Brent A. Strawn ist Privatdozent für Altes Testament an der Candler School of Theology, Emory Universität, Atlanta.; Biographical note: Izaak J. de Hulster is currently a post-doc at the University of Göttingen, Germany. Brent A. Strawn is Associate Professor of Old Testament at Candler School of Theology, Emory University, Atlanta